Mechanism of Governance of Economic Relations - Rus, Andrej (Teorija in Praksa, 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation.
Sociology; Economics
Keywords: economic activity; economic sociology; economics; governance mechanisms; institutional economics; social structure; socioeconomics

Mehanizmi Upravljanja Ekonomskih Odnosov - Rus, Andrej (MECHANISM OF GOVERNANCE OF ECONOMIC RELATIONS., 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation. (English)
Sociology; Economics
Keywords: economic activity; economic sociology; ekonomska sociologija; governance mechanisms; institutional economics; international economic relations; mehanizmi upravljanja; social structure; socioeconomics

Cité et réciprocité, City and Reciprocity : The Role of Cultural Beliefs in the Roman Economy - Verboven, Koenraad (Annales. Histoire, Sciences Sociales, 2012)
La nouvelle économie institutionnelle est devenue populaire dans la recherche de l’économie antique depuis une dizaine d’années. Pourtant la notion de « croyances culturelles », qui joue un rôle central dans l’œuvre de Douglass North et dans les analyses du changement institutionnel par Avner Greif, a été largement ignorée. J’affirme qu’une approche néo-institutionnelle qui utilise cette notion de « croyances culturelles » offre une meilleure voie pour comprendre l’influence des idéologies et des valeurs morales sur l’économie antique que le modèle de Moses Finley. Des croyances culturelles ne sont pas des contraintes déterministes sur le comportement humain, mais elles aident à orienter les prises de décision et permettent d’anticiper les (ré) actions des autres. J’étudie deux ensembles de normes et de valeurs qui, dans la culture romaine, ont profondément marqué le cadre institutionnel de l’économie. L’un était centré sur la réciprocité. Ses normes et valeurs ont permis de construire et de maintenir des réseaux sociaux au-delà du groupe de la familia étendue avec ses affranchis. Elles étaient à la base du développement de la loi des obligations et de la représentation. L’autre se fondait sur la cité. Il a formé la culture politique en créant des droits et des obligations personnelles et en imposant des demandes légitimes aux élites politiques de défendre ceux-ci et de garantir et de stimuler des intérêts privés et communs. Le droit romain et la justice étaient ses résultats les plus importants. Idéologiquement, l’Empire romain se présentait comme une méta-cité qui incorporait les communautés locales qui, à leur tour, étaient graduellement transformées sur le modèle de la cité. Ces deux ensembles de croyances culturelles ont baissé les coûts de transactions, mais ils n’ont jamais menacé la prééminence de l’aristocratie locale et impériale. Vers la fin du IIe siècle de notre ère, les cités locales se sont affaiblies tandis que l’administration impériale se renforçait. Les aristocraties locales et régionales se sont tournées vers la bureaucratie et l’armée impériales pour maintenir leur rang social, leur influence et leur pouvoir. L’idéologie de la cité comme principe dominant de la culture politique devenait soumise à celle de l’empereur sacral, garant de la justice et de l’ordre divins. EN: New Institutional Economics have become popular in ancient economic history research the past decade. However, the notion of “cultural beliefs” that plays a central role in Douglass North’s recent work and in Avner Greif’s analysis of institutional change, has been largely ignored. I argue that a neo-institutional “cultural beliefs approach” offers a better way to understand the influence of ideology and moral values on the ancient economy than the Finley model does. Cultural beliefs are no deterministic constraints on human behavior but help to orient decision making and allow anticipating the (re)actions of others. I explore two key sets of norms and values in Roman culture that profoundly marked the economy’s institutional framework. One centered on reciprocity. Its norms and values supported social networks beyond the confines of the familia-freedmen group and underlay the development of contract and agency law. Another set rested on citizenship. It shaped political culture by creating individual rights and obligations and laying legitimate claims on political elites to enforce these and to take action to secure and stimulate private and common interests. Roman law and the distribution of justice was its prime off-spring. Ideologically the Roman Empire presented itself as a meta-city that incorporated local communities which in turn were gradually transformed to fit the civitas model. Both belief sets lowered transaction costs, but they never threatened the preeminent position of local and imperial aristocracies. Towards the end of the second century CE local communities became weaker while the imperial administration grew stronger. This caused local and regional aristocracies to turn to the imperial court and army for status, influence and power. The ideology of citizenship as the guiding principle of political culture gave way to that of the sacred emperor who guaranteed divine justice and order.
History
Keywords: Roman Empire; ancient economic history; ancient economies; cultural beliefs approach; institutional economics

Polanyi and Hayek on Freedom, the State, and Economics - Filip, Birsen (International Journal of Political Economy, 2012)
This paper examines the relationship that prevails between the state, economics, and freedom according to the works of Friedrich Hayek and Karl Polanyi. Hayek, who was one of the most important contributors to the development of the modern market economy and liberalism, formulated a concept of freedom that includes economic and negative freedom as significant components; his objective was to demonstrate the superiority of liberal capitalist societies over all other forms of organizing a society in terms of achieving freedom. Meanwhile, Polanyi, who confronted all forms of totalitarian regimes and argued that a "self-regulating market … was a utopian project," formulated a concept of freedom that rejected the self-regulating mechanism of the market economy as a component of freedom; he supported regulated markets and included moral, ethical, and social values among the key components required for the realization of freedom. This paper shows that Hayek failed to foresee the destructive social consequences and dehumanizing aspects of modern market capitalism, and promoted the free market economy as a guardian of freedom primarily for its instrumental value. Conversely, Polanyi was able to anticipate the modern market economy's potential to engender disastrous consequences for the whole of humanity and provided an honest and objective analysis of the modern market system that is indispensable for understanding the dilemmas, issues, and contradictions of economic globalization.
Philosophy
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalism; economics; globalization; modern market economy; negative freedom; open society; political philosophy; positive freedom

Adam Smith's Green Thumb and Malthus's Three Horsemen: Cautionary Tales from Classical Political Economy - Dale, Gareth (Journal of Economic Issues (Taylor & Francis Ltd), 2012)
This essay identifies a contradiction between the flourishing interest in the environmental economics of the classical period and a lack of critical parsing of the works of its leading representatives. Its focus is the work of Adam Smith and Thomas Malthus. It offers a critical analysis of their contribution to environmental thought and surveys the work of their contemporary devotees. It scrutinizes Smith's contribution to what Karl Polanyi termed the "economistic fallacy," as well as his defenses of class hierarchy, the "growth imperative" and consumerism. It subjects to critical appraisal Malthus's enthusiasm for private property and the market system, and his opposition to market regulation. While Malthus's principal attraction to ecological economists lies in his having allegedly broadened the scope of economics, and in his narrative of scarcity, this article shows that he, in fact, narrowed the scope of the discipline and conceptualized scarcity in a reified and pseudo-scientific way.
Political Science; History
Keywords: MALTHUS; T. R.; SMITH; Adam; 1723-1790; classical political economy; consumerism; ecological economics; economistic fallacy; environmental economics; environmental policy; growth imperative; natural capital; scarcity

Conventions, the Great Transformation and Actor Network Theory - De Munck, Bert (Konventionen, die große Transformation und Actor Network Theory., 2012)
This article proceeds from the field of tension between the synchronical approach of the economics of convention and the diachronical approach of economic anthropology (in the tradition of Karl Polanyi). It is argued that the economics of convention remain problematic to historians in that they fail to capture the long term transformations traditionally referred to as the emergence of modernity and the coming about of homo economicus. As a possible solution, the use of concepts and insights from Actor Network Theory is proposed. While this cluster of theories enables an historical perspective without considering modernity as a natural process, it confronts changing relationships between subjects, objects and cultural systems of meaning head on.
History
Keywords: CALLON; Michel; actor-network theory; conventions; economic anthropology; economic aspects; history; manners & customs; modernity; performativity

An Analytical Framework for the Relationship between Environmental Measures and Economic Growth Based on the Regulation Theory: Key Concepts and a Simple Model - Okuma, Kazuhiro (Evolutionary and Institutional Economics Review, 2012)
This paper proposes an analytical framework using the regulation approach and consisting of explanations of some concepts and a simple way of modeling; the concepts and modeling are developed by focusing on the distributive aspect of environmental issues and using environmental costs as key indices. As a basis for the framework, we refer to the ideas of Polanyi and the surplus approach, and we recognize the socio-economic system as interlinked triple reproductions of the economy, humans, and the environment. This recognition is formalized as an equation of three-dimensional distributions among profits, wages and rents. The "economy-environment nexus," which represents the relationship between the natural environment's reproduction and economic reproduction, is analyzed as one of the institutional forms. The dynamics of institutional coordination are specified with attention to distributive conflicts between relevant actors, leading to the idea of "spatial and temporal gaps of coordination." Environmental costs are identified and incorporated into the equation of distribution as key information to characterize specific forms of the economy-environment nexus. The economy-environment nexus influences growth regimes through multiple routes, including investment, trade, and productivities. In order to analyze the aggregate effects, we propose a variant of the Kaleckian growth model incorporating environmental costs as key variables. Using this model, we specify conditions for the "paradox of costs for environmental measures," where environmental measures raise the profit rate. This framework is expected to be used in historical or comparative analyses of particular economies, including those using periodized specification of the economy-environment nexus.
Economics
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; distributional effects; employment effects; environment and development; environment and growth; environment and trade; environmental accounts and accounting; environmental equity; pollution control adoption costs; population growth; sustainability

La subsistance de l'homme. La place de l'économie dans l'histoire et la société - Praquin, Nicolas (Comptabilité Contrôle Audit, 2012)
Management Studies
Keywords: La subsistance de l'homme: La place de l'économie dans l'histoire et la société (Book); POLANYI; Karl; 1886-1964; The Livelihood of Man; book review; economic development; nonfiction

Polanyi defanged - Turner, Stephen (Social Studies of Science (Sage Publications, Ltd.), 2012)
A literary criticism of the book "Michael Polanyi and His Generation: Origins of the Social Construction of Science," by Mary Jo Nye is presented. The author discusses the significance of Michael Polanyi in the history of science studies and provides insight on his life and his relationship with his brother Karl. He analyzes how the book presents the origins of science studies, Polanyi’s activities as an economist, and his fight against Communism.
Sociology
Keywords: Dahomey and the Slave Trade; James Bryant Conant; Karl Polanyi; Michael Polanyi & His Generation: Origins of the Social Construction of Science (Book); NYE; Mary Jo; POLANYI; Michael; 1891-1976; communism & science; economists; planning of science; science - study & teaching

The ‘Double Movements’ of Neighbourhood Change: Gentrification and Public Policy in Harlem and Prenzlauer Berg - Bernt, Matthias (Urban Studies (Sage Publications, Ltd.), 2012)
This article explores the interrelation of gentrification and public policies in the neighbourhoods of Prenzlauer Berg (Berlin) and Harlem (New York City). It draws on Karl Polanyi’s concept of a ‘double movement’ and argues that gentrification is fundamentally a political process. Thus, while demise in the face of market forces, or even an active support of gentrification, is clearly visible in both neighbourhoods, the relation between public policies and gentrification is also highly unstable and contradictory. The cases studied highlight that the resources to push or prevent gentrification are contingent; they are not built into the essence of urban development.
Geography; Urban Studies
Keywords: Berlin (Germany); Germany; Harlem (New York; N.Y.); economic conditions; gentrification; government policy; social conditions; urban planning; urban renewal

Addiction: The Urgent Need for a Paradigm Shift - Alexander, Bruce K. (Substance Use & Misuse, 2012)
Severe addictions to drug use and to countless other habits are causing enormous harm around the globe. Massive expenditures and dedicated efforts of police, doctors, addiction therapists, and self-help groups have failed to bring the problem under control, although many individual addicts have been helped. What can society do when our best efforts continue to fail and a menacing problem continues to grow? This paper proposes that a major paradigm shift is required. The currently dominant paradigm assumes that addiction is either an individual disease or an individual moral breach. But this individually oriented paradigm has failed. Instead, addiction needs to be understood socially, as a way that large numbers of people adapt to the breakdown of psychologically sustaining culture under the global influence of free-market society. This new paradigm is based on the social thinking of Karl Polanyi and other social scientists rather than on the individual thinking of neuroscientists, doctors, or psychologists.
Psychology
Keywords: addiction; addictive consumption; alienation; compulsive behavior; economic aspects; free-market society; globalization; paradigm shifts; paradigms (social sciences); psychological factors; psychosocial integration; social problems; social psychology; social support; socioeconomic factors

A second double movement? Polanyi and shifting global opinions on neoliberalism - Levien, Michael; Paret, Marcel (International Sociology, 2012)
Karl Polanyi’s theory of the ‘double movement’ has gained great currency in recent years to explain the global growth of contemporary social movements resisting neoliberalism. However, there has been no statistical research demonstrating whether these protest movements represent a more general trend of growing discontent with ‘disembedding’ markets from public control. This article uses questions from the World Values Survey to construct an ‘embeddedness’ index measuring public opinion on the desired relationship between states and markets. Focusing on public opinion in 20 countries during the 1990s, the analysis poses three questions: First, is there evidence of increasing global support for ‘re-embedding’ markets? Second, how does such opinion vary across regions of the world? Finally, what is the class and gender composition of this latent countermovement? The results provide substantial evidence of an emerging countermovement in public opinion over the 1990s with complex class, gender, and geopolitical variation.
Sociology
Keywords: countermovement; double movement; embeddedness; neoliberalism

China's Decentralized and Inegalitarian Developmental State - Nordhaug, Kristen (Forum for Development Studies, 2012)
This article investigates China's market reforms and rapid economic development from the late 1970s. The following questions are posed: (1) How did the Chinese 'peasant revolution' and the rural policies and institutions of Mao China influence the market reforms and subsequent economic development? (2) How does China's development after the market reforms relate to Marxist and Polanyian notions of proletarization and commodification of land and labour as preconditions of capitalist development? (3) To what extent and why does China's development after the market reforms diverge from East Asian growth with equity? (4) How does China's 'decentralized developmental state' influence its growth model and distribution? (5) The present Chinese government tries to promote greater equality and more domestic consumption. Is this a Polanyian 'double movement' in response to commodification of land and labour? How likely are these policies to succeed? These questions are addressed through historical-comparative analyses with comparisons of long-term rural dynamics of Mao China and the former Soviet Union. China after the market reforms is compared with England during its transition to agrarian capitalism and industrial capitalism from the sixteenth century through the early nineteenth century and with Taiwan and South Korea from the late 1940s until the 1980s.
Development Studies; Economics
Keywords: Marxian; Sraffian; aggregate factor income distribution; current heterodox approaches: socialist; inflation; institutions and growth; institutions: design; formation; and operations; macroeconomic analyses of economic development; money; socialist systems and transitional economies: national income; product; and expenditure; structure; scope; and performance of government

Les sociétés civiles entre risques ploutocratiques de la philanthropie et alternatives solidaires : une lecture polanyienne, The civil societies between the plutocratic risks of philanthropy and solidarity based alternatives : a Polanyian reading - Servet, Jean-Michel (Mondes en développement, 2012)
Tant dans les pays du Nord que dans ceux du Sud, un compromis entre une logique néo-libérale anti-étatiste et certains intérêts des organisations non gouvernementales a marqué la construction des sociétés civiles. Il s’est réalisé notamment à travers le social business soutenu par de grandes entreprises. En mobilisant le concept polanyien de principe d’intégration économique, l’analyse a pour ambition de comprendre les limites de ce nouveau modèle de philanthropie et ce qui le différencie de l’économie solidaire., Both in the Norths and in the Souths, a compromise between a neoliberal anti-statist logic and interests of non governmental organizations marked the construction of civil societies. This is achieved particularly through the social business supported by big companies. By mobilizing the polanyien concept of principle of economic integration, the analysis aims to understand the limits of this new model of philanthropy and what differentiates it of the solidarity based economy.
Development Studies
Keywords: NGOs; Polanyi; formal and informal sectors; institutional arrangements; nonprofit institutions; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; principes d'intégration économique; shadow economy; social business; économie solidaire

Consumer markets and national income inequality: A study of 18 advanced capitalist countries - Kollmeyer, Christopher (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2012)
Sociologists have paid scant attention to the possibility that the structure of the macro-economy is an important determinant of income inequality. Although prior research finds negative links between the size of the public sector and income inequality, no study to date considers whether the size of consumer markets has distributional consequences as well. To investigate this possibility, the present study measures the size of national consumer markets with the System of National Accounts used by governments to calculate gross domestic product (GDP). Based on data from 18 advanced capitalist countries over nearly a 40-year period, two-way random effects regression models reveal a strong and positive link between the size of consumer markets and income inequality. This finding is robust to the inclusion of numerous control variables, and to the consideration of endogeneity within the causal relationship. The proposed theoretical explanation centers on ideas developed by Polanyi, and suggests that economic activity in consumer markets creates higher levels of individual differentiation, and hence higher levels of income inequality, than economic activity in other sectors of the economy. The study concludes by highlighting ways future research can advance our theoretical and empirical understanding of this topic.
Sociology
Keywords: Keynesian economics; Keynesianism; consumer goods; consumer markets; distributive justice; economic aspects; economic sociology; equality - economic aspects; income distribution; income inequality; markets - social aspects; research; social classes; social stratification

Reconfiguring the Politics–Law Relationship in the Integration Project through Conflicts–Law Constitutionalism - Everson, Michelle; Joerges, Christian (European Law Journal, 2012)
This paper argues that the relationship between law and politics must be reconfigured within the European Union. Dissecting recent crises in economic, social and political organisation within Europe with reference to the three ‘fictitious’ commodities of Karl Polanyi, we find that law in Europe has contributed to de-legalisation, de-socialisation and disenfranchisement. Moving on to review the potential for law to respond to crisis through new paradigms of conflict resolution as suggested by Ralf Dahrendorf, we find that the steering capacity of law is nevertheless limited if it fails to establish a sustaining relationship with politics. Our conclusions are modest: conflict–law constitutionalism cannot solve Europe's many crises. However, it does represent a new paradigm of law within which relations between European law and European politics might be re-established—a vital step to overcoming crisis.
Law
Keywords: European Union; constitutionalism; economic law; fictitious commodities

Exchange Rising? Karl Polanyi and Contentious Politics in Contemporary Latin America - Silva, Eduardo (Latin American Politics and Society, 2012)
Free-market reforms in the last quarter of the twentieth century weakened the point of production—labor unions—as the source of effective nonparty political countermovement to liberal capitalism. Has another significant source of societal resistance arisen in association with the resurgence of market economics? Building on the work of Karl Polanyi, this article argues that circuits of exchange—the commodification of labor, land, and money—can be powerful sources of movement against contemporary forms of free-market capitalism. It draws on the cases of Argentina, Bolivia, and Ecuador to explore how Polanyi's exchange-based approach helps to elucidate three phenomena: the great variety of identities behind the myriad movements against free-market capitalism, the emergence of community as a powerful locus for organizing, and the proliferation of new forms of transgressive and highly disruptive direct action to reinforce the debilitated effectiveness of the strike.
Political Science
Keywords: Latin America; circuits of exchange; countermovement

Twentieth-Century Jewish Émigrés and Medieval European Economic History - Mell, Julie (Religions, 2012)
This essay discusses the intellectual contributions of five Jewish émigrés to the study of European economic history. In the midst of the war years, these intellectuals reconceptualized premodern European economic history and established the predominant postwar paradigms. The émigrés form three distinct groups defined by Jewish identity and by professional identity. The first two (Guido Kisch and Toni Oelsner) identified as Jews and worked as Jewish historians. The second two (Michal Postan and Robert Lopez) identified as Jews, but worked as European historians. The last (Karl Polanyi) was Jewish only by origin, identified as a Christian socialist, and worked first as an economic journalist, then in worker's education and late in life as a professor of economics. All five dealt with the origin of European capitalism, but in different veins: Kisch celebrated and Oelsner contested a hegemonic academic discourse that linked the birth of capitalism to Jews. Postan and Lopez contested the flip-side of this discourse, the presumption that medieval Europe was pre-capitalist par excellence. In doing so, they helped construct the current paradigm of a high medieval commercial revolution. Polanyi contested historical narratives that described the Free Market as the natural growth of economic life. This essay explores the grounding of these paradigms in the shared crucible of war and exile as Jewish émigrés. This shared context helps illuminate the significance of their intellectual contributions by uncovering the webs of meaning in which their work was suspended.
History
Keywords: Europe; European economic history; Jewish émigrés; KISCH; Guido; LOPEZ; Robert; OELSNER; Toni; POSTAN; Michael; biographical; economic history; historical literature; identity (philosophical concept); immigrants; intellectuals; medieval economic history; research

Processes of disembedding and displacement: anomie and the juridification of religio-ethnic identity in post-New Order Bali - Ramstedt, Martin (Asian Ethnicity, 2012)
This article applies Karl Polanyi's observation of a double movement of law in the history of nineteenth and early twentieth-century Europe to an analysis of Bali's integration into the global cultural economy. It describes how the increasing disembedding of the island's tourist industry from local norms and institutions, and the parallel disjuncture between Balinese religiosity and Indonesian state religion have created a condition of increasing collective anomie that has in turn provoked endeavors to juridify the Balinese religio-ethnic identity. Conceding the partial success of the juridification process that has been facilitated by the recent governance reform, and that has indeed effected a significant degree of re-embedding both tourism and religion into local culture, the article argues that not only has the anomic condition not been attenuated; the potential for internal conflict and division has even been enhanced.
Law; Anthropology
Keywords: Bali; Balinese (Indonesian people); Europe; POLANYI; Karl; 1886-1964; anomie; decentralization; decentralization in government; disembedding; ethnicity; identity; juridification; religiousness

Solidarity Economy in Brazil: Movement, Discourse and Practice Analysis Through a Polanyian Understanding of the Economy - Lemaître, Andreia; Helmsing, A. H. J. (Bert) (Journal of International Development, 2012)
Solidarity economy (SE) initiatives constitute a worldwide phenomenon that is today at the heart of numerous economic and social debates. They are active in very diverse economic sectors, aiming for example to create employment for poor and low-qualified workers. We begin with presenting a Polanyian framework for the analysis of such economic activities, which enables us to develop a plural and integral conception of a productive organisation. We draw on Polanyi's thesis that economy is a political and institutionalised process and present a historic overview of the construction of the SE ‘sector’ in Brazil. We put forward the hypothesis that the SE today in Brazil represents a social movement. Then, we ask ourselves if the SE movement led to a change in grassroots economic initiatives, such as ‘people's cooperatives’. We present the results of exploratory research undertaken on 15 people's cooperatives in the State of Rio de Janeiro and its conclusions. Copyright © 2012 John Wiley & Sons, Ltd.
Political Science; Development Studies
Keywords: Brazil; inclusion; international development; local development; people's cooperative; social movement; solidarity economy

Problems and opportunities in Polanyian analysis today - Holmes, Christopher (Economy & Society, 2012)
The three books under review in this article all demonstrate the beginnings of a shift in the tone of literature on or derived from the work of Karl Polanyi. On one hand, the authors all show a willingness to admit a variety of problems and weaknesses in his work. But on the other hand, it is precisely this degree of critical introspection that enables the authors under review to identify some of the most important and contemporarily relevant aspects of Polanyi's thought. In the two main sections of this article – on Polanyi's concepts of ‘embeddedness’ and ‘double movement’ – I define the problems highlighted in previous iterations of Polanyian literature, moving on to examine how the texts under review address those problems, laying particular emphasis on the ideational components of Polanyi's thought. I conclude by suggesting future directions for Polanyian scholarship, mooting the possibility of a distinctively ‘post-Polanyian’ perspective in which ideas, discourse and framing are placed centre stage.
Sociology
Keywords: DALE; Gareth; HANN; Chris; HART; Keith; Karl Polanyi: The Limits of the Market (Book); Market & Society: The Great Transformation Today (Book); book review; discourse; double movement; economic anthropology: history; ethnography; critique; economic ideas; embeddedness; nonfiction; post-Polanyi

As especificidades da mercadoria força de trabalho: Marx revisitado - Antonio Vieira, Pedro (The specifities of the labor power commodity: Marx revisited (the labor power commodity: Marx revisited., 2012)
Coming along with Polanyi's ideas of fictitious commodity, this paper seeks to reveal the logical inconsistencies and silents in the economic science arguments on the labor force as a commodity. Once Marx's influence on the anti-capitalist movements is outstanding, we need to show his contribution, through his economic thought, to the scientific economism. As is well known, when proposed that the commodity sell by the worker was the 'labor force' instead the labor, as the classical economists used to say, Marx was able to built his theory on the capitalist economy theory, which relies on the concept of surplus value.. That is the reason why the paper is specially concern with the failures or weaknesses present in one of the huge Marx contribution to the economics thought: the concept of labor force. (English)
Economics
Keywords: MARX; Karl; 1818-1883; anti-globalization movement; capitalists & financiers; commercial products; economics; economism; economists; fictitious commodities; labor force; labor supply; labor-market; labour force; labour market; labour supply; political economy

Neoliberalismo Crisis Actual - Peck, Jamie (Documentos y Aportes en Administración Pública y Gestión Estatal, 2012)
The article discuss the characteristic of the current neoliberalism to understand it as a changeable and complex project whose economic and political sustainability is continuously reinvented and whose governance and spatiality is in need of being understood differently, if a viable alternative is to be constructed. Taking the recent neoliberal crisis as a point of departure, it discusses three main and interrelated aspects: firstly, the polymorphic characteristics of neoliberalism as a process in transformation; secondly, the way in which it could be acted against this neoliberal process by bringing some contributions from Polanyi back into the analysis so as to understand neoliberalism's dynamics; thirdly, the characteristics of some current policies taking place under neoliberal process, some of which could became viable alternatives in the long term. (English)
Geography
Keywords: 21st century; POLANYI; Karl; 1886-1964; crisis; economic history; global financial crisis; 2008-2009; neoliberalism; neoliberalismo; political philosophy; political practices; practical politics; prácticas políticas; world politics - economic aspects

The missing movement: a Polanyian analysis of pre‐crisis America - Herman, Dan (International Journal of Social Economics, 2012)
The purpose of this paper is to seek to apply Polanyi's theory of the double movement as a response to the effects of economic liberalization and globalization to the pre‐2007 American economy. In so doing, it seeks to ascertain the reasons why this assumed double movement did not materialize until after the post‐2007 global economic crisis. Design/methodology/approach – This paper is structured as a theoretical and historical analysis, building upon Polanyi's nineteenth century observations and applying them to contemporary policy economic and social experience in the USA in the late twentieth century. The argument proposes a correlation between the missing and/or delayed movement and the role of access to debt and participation in equity markets. Findings – This paper argues that Polanyi's concept of a societal countermovement has been absent from the post‐1970 period of economic liberalism and globalization until just recently due to an explicit attempt by the forces of capital to circumvent its role in lessening the harmful effects of American capitalism. In particular, the double movement that should have sought to lessen income inequality, unemployment and wage stagnation was instead replaced by access to cheap credit and the democratization of market investments that spurred consumer purchases and a false belief that what was good for the markets was good for working class Americans. Research limitations/implications – This paper highlights the need for ongoing research into the sociotropic nature of trade and of economic policy, and its evolution throughout the contemporary period of economic uncertainty and economic transition. Practical implications – The paper proposes several policy implications arising from the contemporary application of Polanyi's double movement, notably related to international trade and public and political support for ongoing trade liberalization. Social implications – This paper highlights important connections in the relationship between economic policy and the day‐to‐day lives of those who are governed by it. Building on “everyday political economy”, it provides a foundation for arguments that a new balance must be found between economic globalization and transnational capital interests and domestic stability. Originality/value – This paper promotes a novel approach to understanding the political economy of pre‐2007 America, in particular the reflexive nature of economic policy and societal perceptions.
Political Science
Keywords: countermovement; double movement; economic liberalization; global economic crisis; globalization

L'idéologie marchande au service de la biodiversité ? - Tordjman, Hélène; Boisvert, Valérie (Mouvements, 2012)
Economics
Keywords: biodiversity; markets

Retour sur le désencastrement - Brisset, Nicolas (Revue européenne des sciences sociales. European Journal of Social Sciences, 2012)
Our ambition is to point out that a fresh look at what is usualy considered to be Karl Polanyi’s magnum opus, The Great Transformation, opens some new prospects on its analytical. This interpretation qualifies some of the Hungarian author’s main critics, directed against his concept of desembeddedness. With this aim in mind, we re-interpret this debate in epistemological terms, i.e. the link between concepts and reality ; then we try to connect Karl Polanyi with the notion of performativity, which is today flourishing, above all within the field of economic sociology.
Economics
Keywords: Great Transformation; The (Book); Karl Polanyi; disembeddedness; great transformation; performativity; realism

Karl Polanyi: The Limits of the Market - By Gareth Dale - Langton, Robert W. (Political Studies Review, 2012)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Political Science
Keywords: DALE; Gareth; Karl Polanyi: The Limits of the Market (Book); book review; nonfiction

The point is to keep going: the global sub-prime mortgage crisis, local labour market repositioning, and the capital accumulation dynamic in Singapore - Lim, Kean Fan (Journal of Economic Geography, 2012)
The global subprime mortgage crisis in 2007–2008 led to an economic recession in Singapore, but the economy recovered strongly to post a 14.5% expansion in 2010. This article examines how labour market repositioning policies contributed to this recovery. Following Karl Polanyi's conceptualization of the economy as an ‘instituted process’, I explore how these policies function as state-driven redistributive strategies aimed at triggering reciprocal responses from employers and workers within the putatively self-regulatory local labour market. The Singapore case foregrounds the causal roles of place- and time-specific state–firm–labour interactions in precluding what Polanyi calls society's ‘double movement’ against market-driven regulation. This successful preclusion exemplifies how the conditions and relations of economic production are not reproduced solely through market exchange; to sustain the capital accumulation dynamic, complementary acts of reciprocity and redistribution from different socio-economic stakeholders could be equally, if not more, important.
Geography
Keywords: Singapore; capital accumulation dynamic; economic recovery; global financial crisis; instituted economy; labor market; local labour market; saving and investment; spatio-temporal variation; spatio–temporal fix

Development Theory and the Constitution of Market Society: A Polanyian View - Scott, Alan (Comparative Sociology, 2012)
Abstract This paper argues that development studies could benefit from a closer engagement with the arguments of Karl Polanyi. Firstly, a Polanyian perspective gives greater weight to non-economic and non-material factors in making, maintaining and modifying markets. Secondly, it focuses research on the problematic, state- sponsored and contested process of bringing the market actor into being. Finally, a Polanyian approach might better link a, broadly speaking, leftist analysis to 'real world' policy debates about the relative balance between market freedoms and regulation. The conclusion elaborates this final point.
Sociology
Keywords: POLANYI; Karl; 1886-1964; development; disembedding and reembedding; economic development; financial crises; globalization; market making and modifying; mixed economy; neoliberalism; regulation

The peaceful conspiracy: bond markets and international relations during the Pax Britannica - Flandreau, Marc; Flores, Juan H. (International Organization, 2012)
This article provides foundations to K. Polanyi's famed argument that monopoly power in the global capital market served as an instrument of peace during the Pax Britannica (1815-1914). We focus on the role of intermediaries and certification. We show that when information and enforcement are imperfect, there is scope for the endogenous emergence of 'prestigious' intermediaries who enjoy a monopoly position and as a result, control government actions. They can implement conditional lending: they subject the distribution of credit to the adoption of peaceful policies. Prestigious intermediaries act that way because of their concern with maintaining an unblemished track record when wars increased risks of default. Our analysis, which brings together insights from different disciplines, provides a significant extension to, and departure from, recent research on how countries accumulate reputational capital.
History
Keywords: Pax-Britannica; United Kingdom; bond markets; economic history; global capital market (1815-1914); international relations

The roots of the global economic crisis (Respond to this article at http://www.therai.org.uk/at/debate) - Hart, Keith (Anthropology Today, 2012)
The world economic crisis should be seen as an episode in the history of money. “National capitalism” was the main way of organizing money in the twentieth century and its symbol was national monopoly currency. This system has been unravelling since the US dollar de-pegged from gold in 1971. The result is a disconnect between politics which are still largely national and the money circuit which is decentralized and global. The work of Georg Simmel and Karl Polanyi is enrolled to explain this development which entails the loss of money's physical substance, a shift in the social institutions supporting it and a break-up of the forms and functions of “all-purpose money”. The euro crisis reveals the historical mistake of treating market economy as a driver of society and politics. Good intentions at this stage will not reverse what has become a Greek tragedy in more senses than one.
Anthropology
Keywords: global economic crisis

Crise ? Vous avez dit : « Crise » ? - Naszályi, Philippe (Revue des Sciences de Gestion, 2012)
Crisis and institutional environment, crisis and organisational anticipations and crisis and consumer behaviour, just a few of the uses of the word « crisis » ; a word which, for over four years now, for the less perspicacious, and for over thirty years, for those who have been watching the bigger picture, has been the most appropriate word for this stage of development of the contemporary economic system. But exactly « what crisis are we talking about? ». That which is the result of a system, of an ideology which inhabits this system and of which the slightest of abilities was to try and present itself as unable to be exceeded, « by the end of the story ».' Yet, just as Max Weber stated, it seems that today's knowledge is still destined to be exceeded, particularly in the humanities, since society is constantly undergoing transformation. There is, therefore, no economic model which should not be discussed in order to be improved, or replaced. By delving into the ideal of Sismondi, today wrongfully forgotten, or in studying Karl Polanyi, we can gain much support for contemporary reflection which cannot continuously oppose Keynes, often summarised to the deficit of public policies and the « Chicago Boys » of which the action with Augusto Pinochet is truly symbolic of this « neo-liberalism» of American conservatives which is spreading across the globe, despite the crises which it has created. Crisis? Did you say: « Crisis' ? A question, and observation, but also in the manner of «great thinkers », solutions and alternatives which managers, in the widest sense of the term, « those who look after others and their businesses », provide through thirteen articles, collated into three thematic sections in this Spring edition which opens up new areas for reflection and action as « it is indeed time to put production before speculation, future investment before current satisfaction, sustainable employment before immediate profiteering ». (English)
Economics
Keywords: WEBER; Max; 1864-1920; consumer behavior; economic models; economic systems; humanities; institutional environment

Economic and Ecological Crises: Green new deals and no-growth economies - Jessop, Bob (Development, 2012)
Bob Jessop applies cultural political economy to the global economic and ecological crisis. He presents theoretical preliminaries concerning economic and ecological imaginaries, and then goes on to highlight the multidimensional nature of the current crisis and struggles over its interpretation.
Sociology; Development Studies
Keywords: cultural political economy; ecological imaginary; economic imaginary; finance-dominated accumulation; finance-led accumulation; green new deal; neoliberalism; post-neoliberalism

What can Okun teach Polanyi? Efficiency, regulation and equality in the OECD - Hopkin, Jonathan; Blyth, Mark (Review of International Political Economy, 2012)
Arthur Okun famously argued that “effciency is bought at the cost of inequalities in income and wealth”. Okun's trade-off represents the antithesis to Karl Polanyi's view of the relationship that the more embedded markets are in society, the better the social and economic outcomes they produce. This paper refines both these views. We argue that not all forms of market embeddedness are created equal, and that the relationship between equality and efficiency can be both positive and negative. We show this by examining how different ways of embedding economic activity in society through market regulation produce different combinations of efficiency and equality. We identify empirically three broad patterns: market liberal regulatory frameworks that promote competitive markets without decommodifying institutions; embedded liberal regulations that allow markets to work efficiently, but within the framework of decommodification and equality; and embedded illiberalism, where regulations hinder markets in favor of powerful social groups and where decommodification undermines both efficiency and equality. Okun's trade-off emerges as a special case limited to the English-speaking democracies: other OECD countries tend to exhibit either efficiency and equality together, or inefficiency and inequality together. These findings suggest a corrective to both nave market liberal views of the incompatibility of efficiency and equality, but also to the more sophisticated Varieties of Capitalism framework, which pays insufficient attention to the ways in which markets can be embedded in stable but apparently dysfunctional institutional arrangements.
Political Science
Keywords: OECD; OKUN; Arthur; critique; embeddedness; international political economy; regulation

A Polanyian Analysis of Capitalism: A Commentary on Fred Block - Bandelj, Nina (Political Power & Social Theory, 2012)
This chapter responds to Fred Block's article about the weaknesses of the concept of capitalism because of its close association with Marxism, and his proposal for a Polanyian analysis of political economy. In this chapter, I interrogate what may be the commonalities as opposed to divergences between Marx and Polanyi, and I question whether the concept of capitalism is really so wedded to Marxism so as to loose its analytic value, and be better replaced by notions such as market society, or political economy, as used by Polanyi. I agree with Block that a Polanyian analysis importantly widens our view beyond economic reductionism to an understanding of economy and society as co-constitutive. However, I see utility in adding the qualifier "capitalist" to "political economy" to differentiate between socialist and capitalist political economies, for instance, and to properly characterize a system based on private property rights, guided by pursuit of material gain, which advantages some strata in society more than others, leading to endemic social inequality. I propose that a Polanyian focus on society and economy as co-constitutive is more effectively coupled with an analysis that considers capitalism not as a self-driven system of surplus extraction and accumulation, but as an institutional order dependent on political choices. Such a perspective would advance a Polanyian analysis of capitalism.
Sociology; Political Science
Keywords: BLOCK; Fred L.; Marxist philosophy; capitalism; economics; equality; market society; political economy; political science

Varieties of What? Should We Still Be Using the Concept of Capitalism? - Block, Fred (Political Power & Social Theory, 2012)
This article argues that social scientists should reconsider the analytic value of the term "capitalism." The paper argues that the two most coherent definitions of capitalism are those derived from classical Marxism and from the Worm System theory of Immanuel Wallerstein. Marx and Engels' formulation was basically a genetic theory in which the structure of a mode of production is determined by the mode of surplus extraction. During the course of the 20th century, however, Marxist theorists had to modify this framework and the result has been an uncomfortable hybrid. Wallerstein resolved these tensions by redefining capitalism in terms of the logic of a worm system. However, his argument has difficulty in explaining the consequential variations over time in the specific rules and institutional structures that operate at the global level. The article goes on to argue in favor of Karl Polanyi's concept of market society because it focuses attention on the political governance of market societies at both the national and the global levels.
Sociology; Political Science
Keywords: Marxist philosophy; capitalism; mixed economy; political science; public administration; variational principles

Double movements and pendular forces: Polanyian perspectives on the neoliberal age - Dale, Gareth (Current Sociology, 2012)
In the neoliberal era, Karl Polanyi’s notion of the ‘double movement’ has been widely deployed by social scientists as a critique of the prevailing order and a predictor of its demise. This article presents the double movement theorem, drawing upon Polanyi’s published and unpublished writings. It explores parallels between his explanation of the advent of the 19th-century free-market regime in Britain and recent Polanyian accounts of the rise of neoliberalism. Following an analysis of the ‘pendular’ refunctioning of Polanyi’s thesis, it closes by asking whether the recent global financial crisis heralds a pendulum swing from neoliberalism (or ‘market fundamentalism’) towards a form of socially coordinated capitalism, or towards ‘more of the same’. As of 2011, it appears that neoliberal policy and ideology remain hegemonic, not in reinvigorated form but as an ‘undead’ policy regime, one that has spawned a burgeoning literature on ‘zombie capitalism’ and ‘zombie neoliberalism’.
Political Science; Sociology
Keywords: Great Britain; Great Britain - economic conditions - 19th century; crise financière; crisis financiera; double movement; financial crises; financial crisis; free enterprise; international competition; mouvement double; movimiento doble; neoliberalism; neoliberalismo; néolibéralisme; social scientists; zombi; zombie

Marx, Weber, and the "Ceaseless Accumulation of Capital." - Ho-Fung Hung (Political Power & Social Theory, 2012)
Seeing capitalism as a system defined by the imperative of the ceaseless accumulation of capital, instead of using the definition based on wage labor or international trade as Block questions, I argue that the concept of capitalism is still too useful to be abandoned, and cannot be replaced by the Polanyian concept of market in our critique of political economy. As Fernand Braudel and Giovanni Arrighi contend, the capitalist logic of capital accumulation, which is affined to monopoly and state power, is antithetical to the logic of market exchange, which is decentralized and prioritizes livelihoods over profits. Historically, capitalism sometimes made use of the market and sometimes subjugated the market to facilitate accumulation. Likewise, globalization today is a combined movement of expanding free market in certain aspects of life through financial deregulation, privatization, trade liberalization, etc. on the one hand, and exclusion of various processes and costs outside the market through revival of extra-economic coercion, externalization of environmental costs, etc., on the other hand. The imperative of capital accumulation drive capitalists and capitalist states to foster marketization and demarketization in different times and spaces. The critique of and resistance to our capitalist system needs to be antimarket in some instances and pro-market in others. A Polanyian critique of the free market is surely powerful and helpful, but it is not enough for our full understanding of the economic malaises of our times. It is at best counterproductive to throw away the concept of capitalism altogether.
Sociology
Keywords: ARRIGHI; Giovanni; BLOCK; Fred; BRAUDEL; Fernand; 1902-1985; capitalism; economics; globalization; international trade; wages

Dispossession, Class Formation, and the Political Imaginary of Colombia's Coffee Producers Over the Longue Durée: Beyond the Polanyian Analytic - Hough, Phillip A.; Bair, Jennifer (Journal of World-Systems Research, 2012)
For more than a decade, social scientists have been analyzing the implications of the neoliberal turn in development policy and the implications of market-led agrarian reform for agricultural producers in the global South. Among this work is a spate of recent scholarship celebrating a number of flagship movements, such as the Zapatistas in Mexico or the landless movement in Brazil, which are interpreted as efforts by rural communities to resist the threat posed by the commodification of livelihoods and the privatization of natural resources. In this article, we aim to problematize what we diagnose as the "Polanyian analytic" underlying accounts of the current conjuncture which emphasize the imminent potential of neoliberalism to spawn protective counter-movements of the sort described in The Great Transformation. We do so through an analysis of the Unidad Cafetero Nacional (UCN) movement, an organization of Colombian coffee farmers that effectively mobilized large numbers of cafeteros in the 1990s to protest the liberalization of the global coffee market and the decline of state support for the domestic coffee sector. While the UCN may be read as a struggle to resist the dispossession of Colombian coffee farmers, we argue that it represented a particular segment of rural producers who wanted, first and foremost, a restoration of their relatively privileged status within the political economy of Colombian agriculture. Our interpretation of the UCN suggests that whether movements emerge in response to neoliberalism depends on the political imaginaries of the social actors who would create them, and further, that these imaginaries are produced through processes of class formation over the longue durée that shape the meaning of dispossession in particular contexts.
Sociology
Keywords: Colombia; agriculture; coffee growers; coffee plantations; commodification; liberalization (finance); neoliberalism; privatization

On Fred Block, Varieties of What? Should We Still Be Using the Concept of Capitalism? - Streeck, Wolfgang (Political Power & Social Theory, 2012)
There are good reasons for preferring the concept of capitalism over that of "market economy." A capitalist economy is one that depends on the commercialization-through-monetarization of ever more social relations. The result is disequilibrium as the normal condition of a society placed under pressure by its "economy" for continuous reorganization in line with a need for ongoing capital accumulation. A capitalist society enlists the possessive individualism of its members as its principal vehicle of social progress, measured as an increase in wealth-as-money. While Polanyian theory has pointed out important features of advanced capitalist societies, there is no need to sacrifice core Marxian concepts for it. Marxian theory helps avoid the trap of political voluntarism, which stipulates a priority of politics in the capitalist political economy or a fundamental difference between "varieties" of capitalism. Moreover, rather than regarding the capitalist economy as by definition "always embedded," political-economic theory must allow for a self-destructive, and indeed socially destructive, tendency of capitalist political economies to "disembed" themselves by struggling free from social controls and dictating to social life the imperatives of market efficiency and a market-conforming distribution of life chances.
Sociology
Keywords: BLOCK; Fred L.; Marxist philosophy; always embedded economy; capitalism; equilibrium (economics); saving and investment; social control; social theory; varieties of capitalism

Fight or Acquiesce? Religion and Political Process in Turkey's and Egypt's Neoliberalizations - Tuğal, Cihan (Development & Change, 2012)
The Polanyian expectation that disruptive marketization will lead to movements and policies that seek to 'embed' the market in society needs to be tempered by closer scrutiny to historical, religious and political contexts. This article studies how movements respond to marketization. The analysis proceeds through a comparison of the Turkish and Egyptian neoliberalizations, religious movements of the last decades, secular opposition, and finally recent processes, which have led to generally different social takes on neoliberalism. The irony of the Turkish case is that with the empowerment of the Islamists, religious opposition to neoliberalism was muted and secular opposition further marginalized and labelled as 'anti-democratic'. As a result, free market policies were not only sustained, but deepened and intensified, turning Turkey into a neoliberal 'success story'. The (thus far) sustained mobilization of youth and labour in Egypt makes a direct imitation unlikely. Another major factor that would prevent a 'Turkish' solution to Egypt's crisis is the contrasting structure of the religious fields. Moreover, while the passive revolution has further solidified the professional and unified religious field in Turkey, the revolutionary process in Egypt seems to reinforce the fragmentation of the religious field. The article points out that making Islam compatible with neoliberalism would be more difficult in a country with a fragmented religious field, such as Egypt. Although neoliberalism was imposed from above and resisted from below in both nations, in Turkey it came to be embraced in the name of Islam and democracy, whereas in Egypt it remains an imposition and popular struggles against it persist. It is suggested that this process and field-based approach to a Polanyian problem can also shed new light on discussions about 'actually existing neoliberalisms'.
Sociology
Keywords: Egypt; Turkey; Turkey - economic conditions - 1960; economic conditions in Egypt - 1952; economic policy; economics - religious aspects - Islam; neoliberalism; religion & politics

Global Climate Governance: A Legitimation Crisis - Van Vossole, Jonas (Review: A Journal of the Fernand Braudel Center, 2012)
This article frames the failure of COP19 in Warsaw, the problems of the RIO+20 summit, the failure of the Copenhagen COP15, and the problems of the carbon markets within a broader legitimacy crisis of global governance, a consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between Marx-type contestation, referring to emerging classes/states, and Polanyi-type contestation, referring to the victims of global mercantilization. As related to climate governance, the roles of the BRICs in climate negotiations and the global environmental justice movement represent these two types of contestation of the established organizational structures within the global capitalist socio-ecology.
Political Science
Keywords: 21st century; BRICS countries - environmental conditions; BRICS countries - politics & government; MARX; Karl; 1818-1883; alienation; capitalism; climate governance; decision making in environmental policy; globalization & politics; history; organizational legitimacy; power (social sciences); research

Shareholder Engagement in the Embedded Business Corporation: Investment Activism, Human Rights, and TWAIL Discourse - Dhir, Aaron (Business Ethics Quarterly, 2012)
The expansion of extractive corporations’ overseas business opera-tions has led to serious concerns regarding human rights–related impacts. As these apprehensions grow, we see a countervailing rise in calls for government interven-tion and in levels of socially conscious shareholder advocacy. I focus on the latter as manifested in recent use of the shareholder proposal mechanism found in corporate law. Shareholder proposals, while under-theorized, provide a valuable lens through which to consider the argument that economic behaviour is embedded within so-cial relations. In doing so, I situate my analysis within Third World Approaches to International Law (TWAIL) scholarship. Elsewhere, I have supported the use of corporate law tools in advancing the international human rights enterprise and argued that investment activism can be an essential component of this advancement. This paper represents a reflexive pause. Using the case study of a recent proposal submitted to Goldcorp Inc., I seek to problematize the shareholder proposal as a human rights advocacy tool and to examine it as a site of contestation.
Law
Keywords: Third World Approaches to International Law; corporate accountability; corporate law; law; shareholder rights

Embeddedness and regional integration: waiting for Polanyi in a Hayekian setting - Hopner, Martin; Schêfer, Armin (International Organization, 2012)
This article analyzes the social potential of regional integration processes by using the example of European integration. Recent case law from the ECJ has led some observers to argue that judicial decisions increasingly provide European politics with a ôPolanyianö drive. We test this claim by distinguishing three dimensions to European economic and social integration: market-restricting integration, market-enforcing integration, and the creation of a European area of nondiscrimination. We also identify two forms of integration that have different speeds, scopes, and potentials: political integration and judicial integration. The evidence shows that the EU has come closer to Hayek's vision of ôinterstate federalismö than is usually warranted because market-enforcing integration and European nondiscrimination policies have asymmetrically profited from ôintegration through lawö.
Political Science
Keywords: European-integration; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; embeddedness; regional integration; regional-integrationá

The Fundamental and Eternal Conflict - Parguez, Alain (International Journal of Political Economy, 2012)
This contribution aims at exploring what is today the new "normal" in economic policy, namely, austerity. It must be read as a homage to Karl Polanyi, the first who understood the tragedy, and to Kari Polanyi-Levitt, who expanded on her father's thought. Austerity has nothing to do with old anticyclical or stabilizing policies. It is a permanent regime devoid of any sound foundations. It is a pure quasi-religious policy that is self-reinforcing. The author emphasizes the fundamental conflict between its promoter, Friedrich Hayek, and its adversary, John Maynard Keynes, and points to the sole towering intellectual, Karl Polanyi, who understood that their conflict embodied two radically different visions of the world. Polanyi discovered that the core of the conflict was the merciless fight between the supreme rule of God-given market laws, the Hayekian order, and democracy enshrined in a peaceful society that is oriented toward the future. The Hayekian order abolishes the modern democratic state, sacrifices the future, and extols poverty for the sake of order. Polanyi was the first to have discovered the true message of Keynes, who had destroyed the logical foundations of Hayek's philosophy and economics. In conclusion, the author strives to explain why, early in the twenty-first century, the Hayekian legacy is the true road to serfdom because it ignores Polanyi and encourages belief in market laws. Early American "Keynesians," who knew nothing about Hayek, transformed Keynes into a new Léon Walras. These early Keynesians were doomed from the start and vanished when they endorsed the Philips curve as expressing the absolute truth.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; Keynesian economics; The General Theory of Employment; Interest & Money (book); austerity; banking industry – Social aspects; consumption (economics); economic history; employment (economic theory) - social aspects; equilibrium (economics); flexibility; free enterprise; government policy; history of economics - 20th century; international political economy; investments - social aspects; market laws; mixed economy - social aspects; money; money - social aspects; scarcity - social aspects; state

Critique of Current Neoliberalism from a Polanyian Perspective-Politics, Philosophy, and Economics - Seccareccia, Mario (International Journal of Political Economy, 2012)
An introduction is presented which discusses articles within the issue on topics including neoliberalism, the Austrian economist Karl Polanyi's perspective on the history of industrial society during the nineteenth and twentieth centuries and free enterprise.
Economics; Political Science
Keywords: POLANYI; Karl; 1886-1964; free enterprise; neoliberalism; political economy

'Freedom in a Complex Society': The Relevance of Karl Polanyi's Political Philosophy in the Neoliberal Age - Cangiani, Michele (International Journal of Political Economy, 2012)
Karl Polanyi's demanding vision of freedom and democracy seems far from the reality of our times and current ideologies. However, a deeper analysis reveals the ability of his political philosophy not only to find a solution of the paradox of liberty in spite of social constraints, indeed through social institutions, but also to answer the most important practical question with which we are confronted: that of improving, as Polanyi says, "our chances of survival." The conception synthetically expounded in the last pages of The Great Transformation can be better clarified through some of Polanyi's recently published manuscripts of the interwar period. A reference is also to be made to Karl Marx in the first place but also to other more recent authors.
History; Political Science
Keywords: capitalist systems; elections; freedom in a complex society; history of economic thought; legislatures; lobbying; political philosophy; political processes; rent-seeking; voting behavior

The Belief in Economic Determinism, Neoliberalism, and the Significance of Polanyi's Contribution in the Twenty-First Century - Thomasberger, Claus (International Journal of Political Economy, 2012)
How can we explain why Karl Polanyi's book The Great Transformation is more relevant today than ever before? The central thesis of the paper is that Polanyi's analysis is groundbreaking because it goes far beyond the interpretation of the civilization of the nineteenth century. By focusing on the "belief of economic determinism," Polanyi challenges the juxtaposition of being and thinking, of material life-process and consciousness. He rejects the assumption that society encompasses a world of objective facts independent of theoretical beliefs and visions. Polanyi's work is of utmost importance today because by anticipating a change in approach such as the liberal authors made, from the opposite point of view, during the interwar period, he offers the key not only to the analysis of the market mechanism, but also to a critical understanding of neoliberalism.
Economics; Philosophy
Keywords: Austrian school; Austrian school of economics; Great Transformation; The (Book); Keynesian economics; Marxist philosophy; POLANYI; Karl; 1886-1964; belief & doubt - social aspects; central economic planning - social aspects; double movement; economic determinism; economic history - 19th century; economic planning; economic theory; fictitious commodities; free enterprise - social aspects; history of economics - 20th century; human behavior - economic aspects; laissez-faire; neoliberalism; neoliberalism - social aspects; self-fulfilling prophecy; socioeconomics; utopias - economic aspects

'Planning for Freedom': Hayekian and Polanyian Policies in Latin America - Valderrama, Paula (International Journal of Political Economy, 2012)
In the first part of the paper, the concepts of "planning for freedom" by Friedrich Hayek and Karl Polanyi are compared. Hayek rejects "central planning" and also all kinds of "planning for specific aims," but he defends the principle of "planning for competition" as the main condition of a free society. This principle includes the provision of a pertinent institutional framework and state intervention to create markets in spheres of society previously ruled by nonmarket principles. Polanyi agrees that "planning" is necessary in order to achieve freedom in a complex society, but he criticizes the liberal understanding of freedom as a vain "illusion" and considers the principle of "planning for competition" a political ideal that endangers the cohesion of societies. The starting point of Polanyi's argumentation is Karl Marx's theory of reification, but he goes beyond this, complementing it with the concept of "social freedom" based on knowledge and responsibility. Considering the Latin American experience in recent decades, the paper compares Hayekian and Polanyian concepts of "planning for freedom" in their real political and social dimensions.
Philosophy; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Latin America; capitalist systems: planning; coordination; and reform; formal and informal sectors; freedom; history of economic thought: individuals; institutional arrangements; planning models; planning policy; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; shadow economy